The Importance of the Islamic Revolutionary Guard Corps in Ensuring Internal Political Stability - Barseghyan, Davit (History and Culture, 2021)
After the victory of the Islamic Revolution in 1979, Iran continues to be a closed country for a number of reasons. In order to ensure the security of the ruling regime and the security of the state, any kind of information is subject to special examination before it becomes available. This is the reason for the small number of scientific researches on the Iranian armed forces. The work is dedicated to the study of Islamic Revolutionary Guard Corps and aims to determine their significance in ensuring stability in the country.